PTT fiber with low acrolein content and preparation method thereof
By using bis-3-hydroxypropyl 5-aminoisophthalate as a modifier in the preparation process of PTT fibers, thermal oxidation and degradation are inhibited, the problems of acrolein production and release in PTT fibers are solved, and the fibers are improved dyeing performance and safety.
Patent Information
- Application Number
- CN202411462701.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-19
- Publication Date
- 2024-12-13
AI Technical Summary
The prior art is difficult to effectively solve the problem of acrolein production and release during PTT fiber synthesis and processing, affecting the viscosity, hue and production safety of the fiber.
Bis-3-hydroxypropyl 5-aminoisophthalate is used as a modifier to prepare PTT polyester with amino group containing side groups through esterification and polycondensation reaction, inhibit thermal oxidation and degradation, and reduce the generation and release of acrolein.
The acrolein content in PTT fibers is reduced, the acrolein steam release is reduced during spinning, and the dyeing performance and service safety of the fibers are improved.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of polyester fiber production, and in particular to a PTT fiber with low acrolein content and a preparation method thereof. Background Art
[0002] Polytrimethylene terephthalate (PTT) is a new type of polyester. Compared with PET and PBT, fibers made of PTT have higher tensile resilience and lower modulus. They also have the advantages of easy processing, easy dyeing and fluffiness of polyamide fibers. They are currently the best upgraded products. At present, the synthesis of PTT usually adopts the direct esterification method, using purified terephthalic acid (PTA) and 1,3-propylene glycol (PDO) as raw materials, and generating dihydroxypropyl terephthalate (BHPT) and water through esterification reaction. BHPT then generates PTT through polycondensation reaction under the action of polycondensation catalyst. Compared with PET, PTT has poor thermal stability. In addition to the main reaction of generating PTT during the polycondensation process, side reactions such as cleavage of ester bonds between the end groups of the macromolecular chain and in the macromolecular chain will also occur, thereby generating volatile byproduct acrolein, which not only reduces the viscosity of PTT and deteriorates the hue, seriously affecting the subsequent melt spinning and fiber dyeing, but also has high toxicity, strong irritation and tear-inducing effects, and is harmful to human health. The high temperature in the subsequent spinning process will also intensify the cracking of PTT, releasing more acrolein and affecting production safety.
[0003] In response to the problem of acrolein generation, Chinese invention patent CN201780074152.8 removes acrolein by adding aminoamide or primary amine organic small molecules to the polyester system, but the boiling point of most organic amine small molecules is lower than the melt processing temperature of polyester, which will cause them to vaporize and fail. Moreover, the organic amine small molecules introduced into PTT products will also migrate during the service of the products, causing new problems. Chinese invention patent CN106811829B reduces the content of acrolein in polyester fibers by adding 5% to 10% sodium sulfite to the spinning oil bath to absorb acrolein, but affected by the migration rate of acrolein, this method can only remove acrolein on the surface and near the surface of the primary fiber, and cannot solve the problem of acrolein vapor release during the spinning process. Chinese invention patent CN1122061C adds hindered phenol antioxidants in the polycondensation stage of PTT to inhibit thermal cracking by capping the macromolecules, but the cracking of the ester bond does not only occur at the end group. Therefore, there is currently no effective method to solve the problem of acrolein generation and release during the synthesis and processing of PTT, so it is urgent to develop an effective way to remove acrolein generated during the synthesis and spinning of PTT and reduce the acrolein content in PTT fibers. Summary of the invention
[0004] In view of the above-mentioned shortcomings, one object of the present invention is to provide a PTT fiber with low acrolein content, inhibit the volatilization of acrolein during the spinning process and reduce the acrolein content in the PTT fiber. Another object of the present invention is to provide a method for preparing a PTT fiber with low acrolein content, which reduces the generation of acrolein by inhibiting the thermal oxidative degradation in the polymerization stage and the spinning stage, and prevents the instantaneous release of a large amount of acrolein vapor during the spinning process.
[0005] In order to achieve the above technical objectives and meet the above technical requirements, the technical solution adopted by the present invention is:
[0006] A low-acrolein content PTT fiber, characterized in that the raw materials of the PTT fiber include PTT polyester and a modifier, and the modifier is 5-aminoisophthalic acid bis-3-hydroxypropyl ester.
[0007] The present invention also provides a method for preparing a PTT fiber with a low acrolein content, characterized in that it comprises the following steps:
[0008] After the esterification of terephthalic acid and 1,3-propylene glycol, 1,3-propylene terephthalate is obtained, and 1,3-propylene terephthalate and 5-aminoisophthalic acid bis-3-hydroxypropyl ester are polycondensed to obtain PTT polyester, which is pelletized to obtain PTT polyester chips, and the PTT polyester chips are metered, melted, extruded, cooled, oiled and wound to obtain the PTT fiber.
[0009] As a preferred technical solution, the specific steps for preparing 1,3-propylene terephthalate are:
[0010] Terephthalic acid and 1,3-propylene glycol are prepared into slurry, the molar ratio of terephthalic acid to 1,3-propylene glycol is 1:(1.3-1.5), terephthalic acid and 1,3-propylene glycol are subjected to esterification reaction, the pressure is 0.1-0.3 MPa, the temperature is 230-250° C., the reaction time is 70-90 minutes, and when the amount of water distilled in the esterification reaction reaches more than 95% of the theoretical value, the esterification reaction ends, and 1,3-propylene glycol terephthalate is obtained.
[0011] As a preferred technical solution, the specific steps for preparing 5-aminoisophthalic acid bis-3-hydroxypropyl ester are:
[0012] 5-aminoisophthalic acid is dissolved in methanol, thionyl chloride is added in an ice-water bath, the reaction is carried out for 3-4 hours, the methanol is evaporated to remove, water is added to separate the esterification product, and the esterification product is extracted with ethyl acetate, and the ethyl acetate is evaporated to remove to obtain 5-aminoisophthalic acid dimethyl ester;
[0013] 5-aminoisophthalic acid dimethyl ester and 1,3-propylene glycol undergo an ester exchange reaction under the action of a first catalyst, the esterification temperature is 180-210° C., and the esterification time is 2-3 hours until the ester exchange reaction is complete, so as to obtain 5-aminoisophthalic acid bis-3-hydroxypropyl ester, and the first catalyst is zinc acetate.
[0014] As a preferred technical solution, the specific steps for preparing the PTT polyester are:
[0015] After obtaining 1,3-propylene glycol terephthalate, 5-aminoisophthalic acid bis-3-hydroxypropyl ester is added, and then a second catalyst and a stabilizer are added, and a low vacuum stage polycondensation reaction is started under negative pressure conditions. The pressure in this stage is steadily pumped from 0.1-0.3MPa to an absolute pressure below 500Pa, the temperature is controlled at 260-270°C, and the reaction time is 30-50min. Then, the vacuum is continued to be pumped to carry out a high vacuum stage polycondensation reaction. In this stage, the reaction pressure is reduced to an absolute pressure of less than 70Pa, the reaction temperature is controlled at 270-275°C, and the reaction time is 50-90min to obtain the PTT polyester.
[0016] As a preferred technical solution, the intrinsic viscosity of the PTT polyester chips is 1.10-1.20 dL / g, and the content of 5-aminoisophthalic acid bis-3-hydroxypropyl is 3-5wt%.
[0017] As a preferred technical solution, the molar ratio of 5-aminoisophthalic acid, methanol and thionyl chloride is 1:(35.0-37.5):(3-3.5), the volume of water added is 2-3 times that of methanol, the volume of ethyl acetate added is 1-1.2 times that of methanol, the molar ratio of 5-aminoisophthalic acid dimethyl ester to 1,3-propylene glycol is 1:(1.8-2.2), and the amount of zinc acetate added is 0.02%-0.03% of the weight of 5-aminoisophthalic acid dimethyl ester.
[0018] As a preferred technical solution, the second catalyst is tetrabutyl titanate, tetraisopropyl titanate, tetraethyl titanate, stannous acetate or dibutyl tin diacetate, and the amount of the second catalyst added is 0.02%-0.03% of the total weight of terephthalic acid. The stabilizer is triphenyl phosphate, trimethyl phosphate or trimethyl phosphite, and the amount of the stabilizer added is 0.01%-0.03% of the total weight of terephthalic acid.
[0019] As a preferred technical solution, the extrusion temperature is 270-280°C, the cooling temperature is 20-25°C, the cooling wind speed is 2.0-2.5m / s, and the winding speed is 3000-3200m / min.
[0020] As a preferred technical solution, the breaking strength of the PTT fiber is ≥1.9 cN / dtex, the breaking elongation is 120.0±10.0%, and the content of acrolein in the PTT fiber is <2.0 ppm.
[0021] Compared with the traditional technical solution, the beneficial effects of the present invention are:
[0022] The present invention synthesizes the PTT polyester containing amino groups in the side groups by a simple copolymerization method, and achieves the inhibition of thermal oxidative degradation and removal of generated acrolein during polymerization and processing, and reduces the release of acrolein vapor during the spinning process to deteriorate the environment, thereby reducing the acrolein content of the spun PTT fiber, which is beneficial to subsequent fiber dyeing and service safety. DETAILED DESCRIPTION
[0023] An embodiment of the present invention provides a PTT fiber with low acrolein content. The raw materials of the PTT fiber include PTT polyester and a modifier. The modifier is 5-aminoisophthalic acid bis-3-hydroxypropyl ester. The introduced amino group can react with acrolein to remove the generated acrolein.
[0026] The present invention also provides a method for preparing a PTT fiber with a low acrolein content, comprising the following steps:
[0027] After the esterification of terephthalic acid and 1,3-propylene glycol, 1,3-propylene terephthalate is obtained, and 1,3-propylene terephthalate and 5-aminoisophthalic acid bis-3-hydroxypropyl ester are polycondensed to obtain PTT polyester, which is pelletized to obtain PTT polyester chips, and the PTT polyester chips are metered, melted, extruded, cooled, oiled and wound to obtain the PTT fiber.
[0028] The generation of acrolein is reduced by inhibiting the thermal oxidative degradation in the polymerization stage and the spinning stage, thereby preventing the instantaneous release of a large amount of acrolein vapor during the spinning process.
[0029] Terephthalic acid and 1,3-propylene glycol are used as basic polymerization monomers, and dihydroxypropyl terephthalate is generated through esterification reaction. Aromatic amine compounds are added as modifiers, and PTT polyester with amino groups on the side groups is prepared through condensation reaction. Finally, the PTT polyester is melt-spun to obtain PTT fibers with low acrolein content.
[0030] The characteristics of PTT polyester with amino groups in the side groups are as follows: on the one hand, the aniline group in its structure acts as an aromatic amine antioxidant to inhibit the thermal oxidative degradation of macromolecules; on the other hand, the amino group in the structure reacts with the allyl group and aldehyde group of acrolein to undergo Michael addition reaction and Schiff base reaction respectively, so that the acrolein produced by high-temperature pyrolysis is in situ chemically bonded to the macromolecular chain, preventing the instantaneous release of a large amount of acrolein vapor when the PTT polyester melt is extruded from the spinneret during the spinning process, thereby reducing the acrolein content in the PTT fiber and alleviating the migration of acrolein from the PTT fiber during service.
[0031] The present invention synthesizes the PTT polyester containing amino groups in the side groups by a simple copolymerization method, and achieves the inhibition of thermal oxidative degradation and removal of generated acrolein during polymerization and processing, and reduces the release of acrolein vapor during the spinning process to deteriorate the environment, thereby reducing the acrolein content of the spun PTT fiber, which is beneficial to subsequent fiber dyeing and service safety.
[0032] In some embodiments, the specific steps for preparing 1,3-propylene terephthalate are:
[0033] Terephthalic acid and 1,3-propylene glycol are prepared into slurry, the molar ratio of terephthalic acid to 1,3-propylene glycol is 1:(1.3-1.5), terephthalic acid and 1,3-propylene glycol are subjected to esterification reaction, the pressure is 0.1-0.3 MPa, the temperature is 230-250° C., the reaction time is 70-90 minutes, and when the amount of water distilled in the esterification reaction reaches more than 95% of the theoretical value, the esterification reaction ends, and 1,3-propylene glycol terephthalate is obtained.
[0034] In some embodiments, the specific steps for preparing 5-aminoisophthalic acid bis-3-hydroxypropyl ester are:
[0035] 5-aminoisophthalic acid is dissolved in methanol, thionyl chloride is added in an ice-water bath, the reaction is carried out for 3-4 hours, the methanol is evaporated to remove, water is added to separate the esterification product, and the esterification product is extracted with ethyl acetate, and the ethyl acetate is evaporated to remove to obtain 5-aminoisophthalic acid dimethyl ester;
[0036] 5-aminoisophthalic acid dimethyl ester and 1,3-propylene glycol undergo an ester exchange reaction under the action of a first catalyst, the esterification temperature is 180-210° C., and the esterification time is 2-3 hours until the ester exchange reaction is complete, so as to obtain 5-aminoisophthalic acid bis-3-hydroxypropyl ester, and the first catalyst is zinc acetate.
[0037] In some embodiments, the specific steps for preparing the PTT polyester are:
[0038] After obtaining 1,3-propylene glycol terephthalate, 5-aminoisophthalic acid bis-3-hydroxypropyl ester is added, and then a second catalyst and a stabilizer are added, and a low vacuum stage polycondensation reaction is started under negative pressure conditions. The pressure in this stage is steadily pumped from normal pressure 0.1-0.3MPa to an absolute pressure below 500Pa, the temperature is controlled at 260-270°C, and the reaction time is 30-50min. Then, the vacuum is continued to be pumped to carry out a high vacuum stage polycondensation reaction. In this stage, the reaction pressure is reduced to an absolute pressure of less than 70Pa, the reaction temperature is controlled at 270-275°C, and the reaction time is 50-90min to obtain the PTT polyester.
[0039] In some embodiments, the intrinsic viscosity of the PTT polyester chips is 1.10-1.20 dL / g, and the content of 5-aminoisophthalic acid bis-3-hydroxypropyl is 3-5 wt %.
[0040] In some embodiments, the molar ratio of 5-aminoisophthalic acid, methanol, and thionyl chloride is 1:(35.0-37.5):(3-3.5), the volume of water added is 2-3 times that of methanol, the volume of ethyl acetate added is 1-1.2 times that of methanol, the molar ratio of 5-aminoisophthalic acid dimethyl ester to 1,3-propylene glycol is 1:(1.8-2.2), and the amount of zinc acetate added is 0.02%-0.03% of the weight of 5-aminoisophthalic acid dimethyl ester.
[0041] 5-aminoisophthalic acid (commercially available), methanol, and thionyl chloride undergo esterification reaction in an ice-water bath to form 5-aminoisophthalic acid dimethyl ester. In the reaction process, methanol and thionyl chloride first generate the intermediate methyl chloride sulfite, the -OSOCl group in the methyl chloride sulfite is easily separated from the methyl group, and generates sulfurous acid chloride with the free H+ of the carboxylic acid, the sulfurous acid chloride is very easy to decompose so that the reaction has a high yield and reaction rate, and the separated methyl group combines with the carboxylate to form an ester. In addition, due to the steric effect, the amino group on the benzene ring does not participate in the amidation reaction with the carboxylic acid group, and the amino group remains unchanged. The synthesized 5-aminoisophthalic acid dimethyl ester is then subjected to an ester exchange reaction with 1,3-propylene glycol at 180-210°C to obtain the third monomer 5-aminoisophthalic acid bis-3-hydroxypropyl ester, and the by-product is methanol, whose boiling point is much lower than the reaction temperature and is easily evaporated and removed.
[0042] The 5-aminoisophthalic acid bis-3-hydroxypropyl ester used in the present invention belongs to aromatic amines, and its acidity is very weak. It can only take away H+ on the amino nitrogen atom in the presence of a very strong base. Therefore, the 5-aminoisophthalic acid bis-3-hydroxypropyl ester itself does not undergo a condensation reaction with 1,3-propylene glycol, and only participates in the co-condensation reaction of bis-hydroxypropyl terephthalate. However, the presence of amine groups usually causes polyester to be colored, and the coloring effect can be reduced by adding phosphorus compounds such as phosphorous acid or phosphite, and the reaction equation is as follows:
[0043]
[0044] In some embodiments, the second catalyst is tetrabutyl titanate, tetraisopropyl titanate, tetraethyl titanate, stannous acetate or dibutyl tin diacetate, and the amount of the second catalyst added is 0.02%-0.03% of the total weight of terephthalic acid. The stabilizer is triphenyl phosphate, trimethyl phosphate or trimethyl phosphite, and the amount of the stabilizer added is 0.01%-0.03% of the total weight of terephthalic acid.
[0045] In some embodiments, the extrusion temperature is 270-280° C., the cooling temperature is 20-25° C., the cooling wind speed is 2.0-2.5 m / s, and the winding speed is 3000-3200 m / min.
[0046] In some embodiments, the breaking strength of the PTT fiber is ≥1.9 cN / dtex, the breaking elongation is 120.0±10.0%, and the content of acrolein in the PTT fiber is <2.0 ppm.
[0047] Example 1
[0048] A PTT fiber with low acrolein content. The raw materials of the PTT fiber include PTT polyester and a modifier. The modifier is 5-aminoisophthalic acid bis-3-hydroxypropyl ester.
[0049] A method for preparing a PTT fiber with a low acrolein content comprises the following steps:
[0050] After the esterification of terephthalic acid and 1,3-propylene glycol, 1,3-propylene glycol terephthalate is obtained, and 1,3-propylene glycol terephthalate and 5-aminoisophthalic acid bis-3-hydroxypropyl ester are polycondensed to obtain PTT polyester, which is then pelletized to obtain PTT polyester chips, which are metered, melted, extruded, cooled, oiled and wound to obtain the PTT fiber, wherein the intrinsic viscosity of the PTT polyester chips is 1.10 dL / g, and the content of 5-aminoisophthalic acid bis-3-hydroxypropyl ester is 3wt%.
[0051] Extrusion temperature 270°C, cooling temperature 20°C, cooling wind speed 2.0m / s, winding speed 3000m / min.
[0052] The specific steps for preparing 1,3-propylene glycol terephthalate are:
[0053] Terephthalic acid and 1,3-propylene glycol are prepared into slurry, the molar ratio of terephthalic acid to 1,3-propylene glycol is 1:1.3, terephthalic acid and 1,3-propylene glycol are subjected to esterification reaction, the pressure is 0.3 MPa, the temperature is 230°C, the reaction time is 70 minutes, and when the amount of water distilled in the esterification reaction reaches more than 95% of the theoretical value, the esterification reaction ends, and 1,3-propylene terephthalate is obtained.
[0054] The specific steps for preparing 5-aminoisophthalic acid bis-3-hydroxypropyl ester are:
[0055] 5-aminoisophthalic acid is dissolved in methanol, thionyl chloride is added in an ice-water bath, the reaction is carried out for 3 hours, the methanol is evaporated to remove, water is added to separate the esterification product, and the esterification product is extracted with ethyl acetate, and the ethyl acetate is evaporated to remove to obtain 5-aminoisophthalic acid dimethyl ester;
[0056] 5-aminoisophthalic acid dimethyl ester and 1,3-propylene glycol are subjected to an ester exchange reaction under the action of a first catalyst, the esterification temperature is 180° C., and the esterification time is 2 hours until the ester exchange reaction is complete, so as to obtain 5-aminoisophthalic acid bis-3-hydroxypropyl ester, and the first catalyst is zinc acetate.
[0057] The specific steps for preparing the PTT polyester are:
[0058] After obtaining 1,3-propylene glycol terephthalate, 5-aminoisophthalic acid bis-3-hydroxypropyl ester is added, and then a second catalyst and a stabilizer are added, and a low vacuum stage condensation reaction is started under negative pressure conditions. The pressure in this stage is steadily pumped from 0.3MPa to an absolute pressure below 500Pa, the temperature is controlled at 260°C, and the reaction time is 30min. Then, the vacuum is continued to be pumped to carry out a high vacuum stage condensation reaction. In this stage, the reaction pressure is reduced to an absolute pressure of less than 70Pa, the reaction temperature is controlled at 270°C, and the reaction time is 50min, thereby obtaining the PTT polyester.
[0059] The molar ratio of 5-aminoisophthalic acid, methanol and thionyl chloride is 1:35.0:3, the volume of water added is twice that of methanol, the volume of ethyl acetate added is 1 time that of methanol, the molar ratio of 5-aminoisophthalic acid dimethyl ester and 1,3-propylene glycol is 1:1.8, and the amount of zinc acetate added is 0.02% of the weight of 5-aminoisophthalic acid dimethyl ester.
[0060] The second catalyst is tetrabutyl titanate, and the amount of the second catalyst added is 0.02% of the total weight of terephthalic acid. The stabilizer is triphenyl phosphate, and the amount of the stabilizer added is 0.01% of the total weight of terephthalic acid.
[0061] The performance test of the PTT fiber prepared in Example 1 showed that the breaking strength of the PTT fiber was 2.10 cN / dtex, the breaking elongation was 110%, and the content of acrolein in the PTT fiber was 1.8 ppm.
[0062] Example 2
[0063] A PTT fiber with low acrolein content. The raw materials of the PTT fiber include PTT polyester and a modifier. The modifier is 5-aminoisophthalic acid bis-3-hydroxypropyl ester.
[0064] A method for preparing a PTT fiber with a low acrolein content comprises the following steps:
[0065] After the esterification of terephthalic acid and 1,3-propylene glycol, 1,3-propylene glycol terephthalate is obtained, and 1,3-propylene glycol terephthalate and 5-aminoisophthalic acid bis-3-hydroxypropyl ester are polycondensed to obtain PTT polyester, which is then pelletized to obtain PTT polyester chips, which are metered, melted, extruded, cooled, oiled and wound to obtain the PTT fiber, wherein the intrinsic viscosity of the PTT polyester chips is 1.15 dL / g, and the content of 5-aminoisophthalic acid bis-3-hydroxypropyl ester is 4wt%.
[0066] Extrusion temperature 275°C, cooling temperature 22°C, cooling wind speed 2.3m / s, winding speed 3100m / min.
[0067] The specific steps for preparing 1,3-propylene glycol terephthalate are:
[0068] Terephthalic acid and 1,3-propylene glycol are prepared into slurry, the molar ratio of terephthalic acid to 1,3-propylene glycol is 1:1.4, terephthalic acid and 1,3-propylene glycol are subjected to esterification reaction, the pressure is 0.3 MPa, the temperature is 240°C, the reaction time is 80 minutes, and when the amount of water distilled in the esterification reaction reaches more than 95% of the theoretical value, the esterification reaction ends, and 1,3-propylene terephthalate is obtained.
[0069] The specific steps for preparing 5-aminoisophthalic acid bis-3-hydroxypropyl ester are:
[0070] 5-aminoisophthalic acid was dissolved in methanol, thionyl chloride was added in an ice-water bath, the reaction was continued for 3.5 hours, the methanol was evaporated to remove, water was added to separate the esterification product, the esterification product was extracted with ethyl acetate, and the ethyl acetate was evaporated to remove the ethyl acetate to obtain 5-aminoisophthalic acid dimethyl ester;
[0071] 5-aminoisophthalic acid dimethyl ester and 1,3-propylene glycol are subjected to an ester exchange reaction under the action of a first catalyst, the esterification temperature is 190° C., and the esterification time is 2.5 hours until the ester exchange reaction is complete, to obtain 5-aminoisophthalic acid bis-3-hydroxypropyl ester, and the first catalyst is zinc acetate.
[0072] The specific steps for preparing the PTT polyester are:
[0073] After obtaining 1,3-propylene glycol terephthalate, 5-aminoisophthalic acid bis-3-hydroxypropyl ester is added, and then a second catalyst and a stabilizer are added, and a low vacuum stage condensation reaction is started under negative pressure conditions. The pressure in this stage is steadily pumped from 0.3MPa to an absolute pressure below 500Pa, the temperature is controlled at 265°C, and the reaction time is 40min. Then, the vacuum is continued to be pumped to carry out a high vacuum stage condensation reaction. In this stage, the reaction pressure is reduced to an absolute pressure of less than 70Pa, the reaction temperature is controlled at 272°C, and the reaction time is 70min, thereby obtaining the PTT polyester.
[0074] The molar ratio of 5-aminoisophthalic acid, methanol and thionyl chloride is 1:36:3.5, the volume of water added is 2 times that of methanol, the volume of ethyl acetate added is 1.2 times that of methanol, the molar ratio of 5-aminoisophthalic acid dimethyl ester and 1,3-propylene glycol is 1:2, and the amount of zinc acetate added is 0.025% of the weight of 5-aminoisophthalic acid dimethyl ester.
[0075] The second catalyst is tetraisopropyl titanate, and the amount of the second catalyst added is 0.025% of the total weight of terephthalic acid. The stabilizer is trimethyl phosphate, and the amount of the stabilizer added is 0.02% of the total weight of terephthalic acid.
[0076] The performance test of the PTT fiber prepared in Example 2 showed that the breaking strength of the PTT fiber was 2.07 cN / dtex, the breaking elongation was 123%, and the content of acrolein in the PTT fiber was 1.6 ppm.
[0077] Example 3
[0078] A PTT fiber with low acrolein content. The raw materials of the PTT fiber include PTT polyester and a modifier. The modifier is 5-aminoisophthalic acid bis-3-hydroxypropyl ester.
[0079] A method for preparing a PTT fiber with a low acrolein content comprises the following steps:
[0080] After the esterification of terephthalic acid and 1,3-propylene glycol, 1,3-propylene glycol terephthalate is obtained, and 1,3-propylene glycol terephthalate and 5-aminoisophthalic acid bis-3-hydroxypropyl ester are polycondensed to obtain PTT polyester, which is then pelletized to obtain PTT polyester chips, which are metered, melted, extruded, cooled, oiled and wound to obtain the PTT fiber, wherein the intrinsic viscosity of the PTT polyester chips is 1.20 dL / g, and the content of 5-aminoisophthalic acid bis-3-hydroxypropyl ester is 5wt%.
[0081] Extrusion temperature 280°C, cooling temperature 25°C, cooling wind speed 2.5m / s, winding speed 3200m / min.
[0082] The specific steps for preparing 1,3-propylene glycol terephthalate are:
[0083] Terephthalic acid and 1,3-propylene glycol are prepared into slurry, the molar ratio of terephthalic acid to 1,3-propylene glycol is 1:1.5, terephthalic acid and 1,3-propylene glycol are subjected to esterification reaction, the pressure is 0.3 MPa, the temperature is 250°C, the reaction time is 90 minutes, and when the amount of water distilled in the esterification reaction reaches more than 95% of the theoretical value, the esterification reaction ends, and 1,3-propylene terephthalate is obtained.
[0084] The specific steps for preparing 5-aminoisophthalic acid bis-3-hydroxypropyl ester are:
[0085] 5-aminoisophthalic acid is dissolved in methanol, thionyl chloride is added in an ice-water bath, the reaction is carried out for 4 hours, the methanol is evaporated to remove, water is added to separate the esterification product, and the esterification product is extracted with ethyl acetate, and the ethyl acetate is evaporated to remove to obtain 5-aminoisophthalic acid dimethyl ester;
[0086] 5-aminoisophthalic acid dimethyl ester and 1,3-propylene glycol are subjected to an ester exchange reaction under the action of a first catalyst, the esterification temperature is 210° C., and the esterification time is 3 hours until the ester exchange reaction is complete, thereby obtaining 5-aminoisophthalic acid bis-3-hydroxypropyl ester, and the first catalyst is zinc acetate.
[0087] The specific steps for preparing the PTT polyester are:
[0088] After obtaining 1,3-propylene glycol terephthalate, 5-aminoisophthalic acid bis-3-hydroxypropyl ester is added, and then a second catalyst and a stabilizer are added, and a low vacuum stage condensation reaction is started under negative pressure conditions. The pressure in this stage is steadily pumped from 0.3MPa to an absolute pressure below 500Pa, the temperature is controlled at 270°C, and the reaction time is 50min. Then, the vacuum is continued to be pumped to carry out a high vacuum stage condensation reaction. In this stage, the reaction pressure is reduced to an absolute pressure of less than 70Pa, the reaction temperature is controlled at 275°C, and the reaction time is 90min, thereby obtaining the PTT polyester.
[0089] The molar ratio of 5-aminoisophthalic acid, methanol and thionyl chloride is 1:37.5:3.5, the volume of water added is 3 times that of methanol, the volume of ethyl acetate added is 1.2 times that of methanol, the molar ratio of 5-aminoisophthalic acid dimethyl ester and 1,3-propylene glycol is 1:2.2, and the amount of zinc acetate added is 0.03% of the weight of 5-aminoisophthalic acid dimethyl ester.
[0090] The second catalyst is tetrabutyl titanate, and the amount of the second catalyst added is 0.03% of the total weight of terephthalic acid. The stabilizer is triphenyl phosphate, trimethyl phosphate or trimethyl phosphite, and the amount of the stabilizer added is 0.03% of the total weight of terephthalic acid.
[0091] The performance test of the PTT fiber prepared in Example 3 showed that the breaking strength of the PTT fiber was 2.20 cN / dtex, the breaking elongation was 130%, and the content of acrolein in the PTT fiber was 1.5 ppm.
[0092] It can be seen from Example 1, Example 2 and Example 3 that the content of acrolein is very low, the elimination effect of acrolein is good, and the mechanical properties are good.
[0093] Any numerical value cited herein includes all values of lower and upper values that increase by one unit from the lower limit to the upper limit, and there is at least a two-unit interval between any lower value and any higher value. For example, if the value of the quantity of a component or a process variable (such as temperature, pressure, time, etc.) is stated to be from 1 to 90, preferably from 20 to 80, and more preferably from 30 to 70, the purpose is to illustrate that values such as 15 to 85, 22 to 68, 43 to 51, 30 to 32 are also explicitly listed in the specification. For values less than 1, one unit is appropriately considered to be 0.0001, 0.001, 0.01, 0.1. These are merely examples that are intended to be clearly expressed, and it can be considered that all possible combinations of numerical values listed between the lowest value and the highest value are clearly stated in the specification in a similar manner.
[0094] Unless otherwise indicated, all ranges include the endpoints and all numbers between the endpoints. "About" or "approximately" used with a range applies to both endpoints of the range. Thus, "about 20 to 30" is intended to cover "about 20 to about 30", including at least the specified endpoints.
[0095] All articles and references disclosed, including patent applications and publications, are incorporated herein by reference for all purposes. The term "consisting essentially of..." to describe a combination should include the identified elements, ingredients, parts or steps and other elements, ingredients, parts or steps that do not substantially affect the basic novel characteristics of the combination. The use of the terms "comprising" or "including" to describe a combination of elements, ingredients, parts or steps herein also contemplates embodiments that consist essentially of these elements, ingredients, parts or steps. By using the term "may", it is intended to indicate that any attribute described that "may" include is optional.
[0096] Multiple elements, ingredients, parts or steps can be provided by a single integrated element, ingredient, part or step. Alternatively, a single integrated element, ingredient, part or step can be divided into separate multiple elements, ingredients, parts or steps. The disclosure "one" or "an" used to describe an element, ingredient, part or step is not intended to exclude other elements, ingredients, parts or steps.
[0097] It should be understood that the above description is for illustration and not for limitation. Many embodiments and many applications beyond the examples provided will be apparent to those skilled in the art upon reading the above description. Therefore, the scope of the present teachings should not be determined with reference to the above description, but should be determined with reference to the appended claims and the full scope of equivalents possessed by such claims. For the purpose of comprehensiveness, all articles and references, including disclosures of patent applications and publications, are incorporated herein by reference. The omission of any aspect of the subject matter disclosed herein in the preceding claims is not intended to be a waiver of the subject matter, nor should it be considered that the inventors did not consider the subject matter to be part of the disclosed inventive subject matter.
Claims
1. A low acrolein content PTT fiber, characterized in that: The raw materials of the PTT fiber include PTT polyester and a modifier, and the modifier is 5-aminoisophthalic acid bis-3-hydroxypropyl ester.
2. The method for preparing low acrolein content PTT fiber according to claim 1, characterized in that: The following steps are involved: After the esterification of terephthalic acid and 1,3-propylene glycol, 1,3-propylene terephthalate is obtained, and 1,3-propylene terephthalate and 5-aminoisophthalic acid bis-3-hydroxypropyl ester are polycondensed to obtain PTT polyester, which is pelletized to obtain PTT polyester chips, and the PTT polyester chips are metered, melted, extruded, cooled, oiled and wound to obtain the PTT fiber.
3. The method for preparing low acrolein content PTT fiber according to claim 2, characterized in that: The specific steps for preparing 1,3-propylene glycol terephthalate are: Terephthalic acid and 1,3-propylene glycol are prepared into slurry, the molar ratio of terephthalic acid to 1,3-propylene glycol is 1:(1.3-1.5), terephthalic acid and 1,3-propylene glycol are subjected to esterification reaction, the pressure is 0.1-0.3 MPa, the temperature is 230-250° C., the reaction time is 70-90 minutes, and when the amount of water distilled in the esterification reaction reaches more than 95% of the theoretical value, the esterification reaction ends, and 1,3-propylene glycol terephthalate is obtained.
4. The method for preparing low acrolein content PTT fiber according to claim 2, characterized in that: The specific steps for preparing 5-aminoisophthalic acid bis-3-hydroxypropyl ester are: 5-aminoisophthalic acid is dissolved in methanol, thionyl chloride is added in an ice-water bath, the reaction is carried out for 3-4 hours, the methanol is evaporated to remove, water is added to separate the esterification product, and the esterification product is extracted with ethyl acetate, and the ethyl acetate is evaporated to remove to obtain 5-aminoisophthalic acid dimethyl ester; 5-aminoisophthalic acid dimethyl ester and 1,3-propylene glycol undergo an ester exchange reaction under the action of a first catalyst, the esterification temperature is 180-210° C., and the esterification time is 2-3 hours until the ester exchange reaction is complete, so as to obtain 5-aminoisophthalic acid bis-3-hydroxypropyl ester, and the first catalyst is zinc acetate.
5. The method for preparing low acrolein content PTT fiber according to claim 3, characterized in that: The specific steps for preparing the PTT polyester are: After obtaining 1,3-propylene glycol terephthalate, 5-aminoisophthalic acid bis-3-hydroxypropyl ester is added, and then a second catalyst and a stabilizer are added, and a low vacuum stage polycondensation reaction is started under negative pressure conditions. The pressure in this stage is steadily pumped from 0.1-0.3MPa to an absolute pressure below 500Pa, the temperature is controlled at 260-270°C, and the reaction time is 30-50min. Then, the vacuum is continued to be pumped to carry out a high vacuum stage polycondensation reaction. In this stage, the reaction pressure is reduced to an absolute pressure of less than 70Pa, the reaction temperature is controlled at 270-275°C, and the reaction time is 50-90min to obtain the PTT polyester.
6. The method for preparing low acrolein content PTT fiber according to claim 2, characterized in that: The intrinsic viscosity of the PTT polyester chips is 1.10-1.20 dL / g, and the content of 5-aminoisophthalic acid bis-3-hydroxypropyl is 3-5 wt %.
7. The method for preparing low acrolein content PTT fiber according to claim 4, characterized in that: The molar ratio of 5-aminoisophthalic acid, methanol and thionyl chloride is 1:(35.0-37.5):(3-3.5), the volume of water added is 2-3 times that of methanol, the volume of ethyl acetate added is 1-1.2 times that of methanol, the molar ratio of 5-aminoisophthalic acid dimethyl ester and 1,3-propylene glycol is 1:(1.8-2.2), and the amount of zinc acetate added is 0.02%-0.03% of the weight of 5-aminoisophthalic acid dimethyl ester.
8. The method for preparing low acrolein content PTT fiber according to claim 5, characterized in that: The second catalyst is tetrabutyl titanate, tetraisopropyl titanate, tetraethyl titanate, stannous acetate or dibutyl tin diacetate, and the amount of the second catalyst added is 0.02%-0.03% of the total weight of terephthalic acid. The stabilizer is triphenyl phosphate, trimethyl phosphate or trimethyl phosphite, and the amount of the stabilizer added is 0.01%-0.03% of the total weight of terephthalic acid.
9. The method for preparing low acrolein content PTT fiber according to claim 2, characterized in that: Extrusion temperature 270-280℃, cooling temperature 20-25℃, cooling wind speed 2.0-2.5m / s, winding speed 3000-3200m / min.
10. The method for preparing low acrolein content PTT fiber according to claim 2, characterized in that: The breaking strength of the PTT fiber is ≥1.9 cN / dtex, the breaking elongation is 120.0±10.0%, and the content of acrolein in the PTT fiber is <2.0 ppm.
